A medical sodium hyaluronate gel and preparation method thereof
By adding modified sodium hyaluronate, anti-degradable agent and synergist to prepare medical sodium hyaluronate gel and dialysis treatment, the problem that gels in the prior art cannot have both anti-degradable ability and low toxicity, and achieve stronger anti-degradable ability and lower toxicity.
Patent Information
- Application Number
- CN202411910705.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-04
AI Technical Summary
The medical sodium hyaluronate gel prepared by the prior art cannot have both anti-degradation ability and low toxicity.
By adding modified sodium hyaluronate, anti-degradable agent and synergist to deionized water and dialysis treatment, a modified sodium hyaluronate gel with a specific molecular weight is prepared to improve its anti-degradation ability and reduce toxicity.
The prepared medical sodium hyaluronate gel has stronger anti-degradation ability and extremely low cytotoxicity, and has a wider application prospect.
Smart Images

Figure BDA0005205578210000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and in particular to a medical sodium hyaluronate gel and a preparation method thereof. Background Art
[0002] Hyaluronic acid is a mucopolysaccharide widely found in tissues such as skin, ligaments, joint fluid and vitreous humor of the eyes.
[0003] Sodium hyaluronate is the sodium salt of hyaluronic acid, an inherent component in the human body. It is a glucuronic acid with no species specificity. It is widely present in tissues and organs such as the placenta, amniotic fluid, lens, articular cartilage, and skin dermis. It is distributed in the cytoplasm and interstitial matrix, and plays a lubricating and nourishing role on the cells and cell organs contained therein. Sodium hyaluronate has a very strong moisturizing ability, can absorb and lock a large amount of water, and provide lasting moisturizing for the skin. Therefore, it is widely used in skin care products and cosmetics to improve problems such as dry skin and dehydration; sodium hyaluronate can inhibit inflammatory reactions and relieve inflammatory symptoms. In medicine, it is often used to treat inflammatory diseases such as arthritis and stomatitis to relieve patients' pain and discomfort; sodium hyaluronate can promote cell proliferation and movement and accelerate wound healing. In the treatment of surgical operations, burns, trauma, etc., sodium hyaluronate can be used as an auxiliary therapeutic drug to increase the healing rate; sodium hyaluronate is the main component in the joint cavity, has a lubricating and buffering effect, and can protect the joints from wear. When treating joint diseases, sodium hyaluronate can be injected into the joint cavity to relieve joint pain and stiffness. Sodium hyaluronate is also widely used in the field of ophthalmology, such as for treating dry eyes, keratitis and other eye diseases, or for protecting the cornea and other eye structures in ophthalmic surgery. In short, sodium hyaluronate is a biopolymer with multiple functions, which is widely used in the fields of medicine and beauty.
[0004] Natural sodium hyaluronate is easily dispersed and degraded by enzymes and free radicals present in body tissues. The material obtained by introducing a cross-linking agent to cross-link the chain sodium hyaluronate to form a network structure can overcome the defects of the above-mentioned natural sodium hyaluronate material to a certain extent, increase the degree of cross-linking, and prolong the degradation time of the sodium hyaluronate gel, thereby prolonging the retention time of the sodium hyaluronate gel after injection.
[0005] However, most of the existing cross-linking agents are toxic or potentially toxic; and the dosage requirements are also high. When the amount of cross-linking agent used is small, the degree of cross-linking is low, the prepared gel material has weak resistance to enzymatic hydrolysis, and the time it stays in the body is relatively short.
[0006] Therefore, according to the above-mentioned related technologies, it is urgent to develop a medical sodium hyaluronate gel and a preparation method thereof. Summary of the invention
[0007] In view of this, the purpose of the present invention is to provide a medical sodium hyaluronate gel and a preparation method thereof, so as to solve the problem that the medical sodium hyaluronate gel prepared in the prior art cannot have both anti-degradation ability and low toxicity.
[0008] Based on the above purpose, the present invention provides a medical sodium hyaluronate gel and a preparation method thereof.
[0009] A method for preparing medical sodium hyaluronate gel comprises the following steps:
[0010] Add modified sodium hyaluronate to deionized water, adjust the pH to 7.3-7.5 with sodium hydroxide solution, then add antidegradant and synergist in sequence and mix well to obtain medical sodium hyaluronate gel;
[0011] The mass ratio of the deionized water, modified sodium hyaluronate, antidegradant and synergist is 400-500:12-15:4.8-6:7.2-9;
[0012] The modified sodium hyaluronate is prepared from sodium hyaluronate powder, N-hydroxysuccinimide, carbodiimide, and cysteamine hydrochloride;
[0013] The antidegradation agent is prepared by heat-treating raw silk with lithium bromide solution after degumming;
[0014] The synergist is prepared from sodium alginate, sodium periodate and ethylene glycol.
[0015] Preferably, the preparation method of the modified sodium hyaluronate is as follows:
[0016] Step A1: dissolving sodium hyaluronate powder in deionized water, then sequentially adding N-hydroxysuccinimide and carbodiimide, and then adjusting the pH to 4.7-4.75 with hydrochloric acid solution, and activating for 1.7-2 hours to obtain a pre-modified sodium hyaluronate mixture;
[0017] Step A2: Add cysteamine hydrochloride to the pre-modified sodium hyaluronate mixture, adjust the pH to 4.7-4.75 with sodium hydroxide solution, react for 24-25 hours under light-proof conditions, put into a dialysis bag, dialyze with deionized water for 3-6 days, and obtain modified sodium hyaluronate after freeze-drying.
[0018] Preferably, the molecular weight of the sodium hyaluronate powder in step A1 is 40-300 kDa;
[0019] The mass ratio of the sodium hyaluronate powder, deionized water, N-hydroxysuccinimide and carbodiimide in step A1 is 20-25:4000-5000:11.5-14:28.7-30.
[0020] Preferably, the mass ratio of the pre-modified sodium hyaluronate mixture and cysteamine hydrochloride in step A2 is 4060-5069:17-20;
[0021] The molecular weight cut-off of the dialysis bag in step A2 is 8-12 kDa.
[0022] Preferably, the preparation method of the antidegradant is as follows:
[0023] Step B1: boiling raw silk in a sodium carbonate aqueous solution for 3-5 times, each time for 30-35 minutes, rinsing with deionized water and drying at 55-60° C. to obtain degummed fibers;
[0024] Step B2: dissolving the degummed fiber in a lithium bromide solution at 58-62° C. and stirring for 60-70 minutes, putting the fiber into a dialysis bag after cooling, dialyzing it with deionized water for 3-6 days, filtering it with absorbent cotton, centrifuging it at 10000-11000 rpm for 5-8 minutes, and freeze-drying it to obtain an antidegradant.
[0025] Preferably, the ratio of raw silk to sodium carbonate aqueous solution in step B1 is 80-100 g: 4-5 L;
[0026] The concentration of the sodium carbonate aqueous solution in step B1 is 0.0045-0.005 mol / L.
[0027] Preferably, the mass ratio of the degummed fiber to the lithium bromide solution in step B2 is 10-15 g: 100-140 mL;
[0028] The concentration of the lithium bromide solution in step B2 is 9-9.3 mol / L;
[0029] The molecular weight cut-off of the dialysis bag in step B2 is 9-12 kDa.
[0030] Preferably, the preparation method of the synergist is as follows:
[0031] Sodium alginate was dissolved in deionized water, and then sodium periodate aqueous solution was added while stirring. Ethylene glycol was added after 115-120 minutes, and the reaction was continued for 55-60 minutes. The mixture was put into a dialysis bag, dialyzed with deionized water for 3-6 days, and then freeze-dried to obtain a synergist.
[0032] Preferably, the concentration of the sodium periodate aqueous solution is 107-110 g / L.
[0033] Preferably, the dosage ratio of the sodium alginate, deionized water, sodium periodate aqueous solution, and ethylene glycol is 10-15 g: 500-750 mL: 50-75 mL: 3-4.5 mL;
[0034] The molecular weight cut-off of the dialysis bag is 8-10 kDa.
[0035] Beneficial effects of the present invention:
[0036] The present invention provides a medical sodium hyaluronate gel and a preparation method thereof. The cross-linking agent used in the modification of sodium hyaluronate by the present invention is less toxic, and the present invention also performs a dialysis treatment on it during the modification process, that is, a modified sodium hyaluronate of a specific molecular weight is obtained, and its toxicity is further reduced. At the same time, the antidegradant and synergist added are also non-toxic substances, so the sodium hyaluronate gel prepared by the present invention has extremely low toxicity; and the present invention performs a dialysis treatment during the preparation of the antidegradant, synergist, and modified sodium hyaluronate, and by using a dialysis bag with a specific molecular weight cutoff, an antidegradant, synergist, and modified sodium hyaluronate that can be cross-linked are obtained, so that the anti-degradation ability of the sodium hyaluronate gel is further improved. Therefore, compared with the prior art, the medical sodium hyaluronate gel prepared by the present invention has better anti-degradation ability, lower toxicity, and wider application prospects. DETAILED DESCRIPTION
[0037] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0038] Example 1: A method for preparing a medical sodium hyaluronate gel is as follows:
[0039] S1: 20 g of sodium hyaluronate powder with a molecular weight of 40-300 kDa was dissolved in 4000 g of deionized water, and then 11.5 g of N-hydroxysuccinimide and 28.7 g of carbodiimide were added in sequence, and the pH was adjusted to 4.7 with a hydrochloric acid solution, and activated for 1.7 hours to obtain a pre-modified sodium hyaluronate mixture;
[0040] S2: Add 17 g of cysteamine hydrochloride to 4060 g of the pre-modified sodium hyaluronate mixture, adjust the pH to 4.7 with sodium hydroxide solution, react for 24 h in a dark environment, put into a dialysis bag with a molecular weight cutoff of 8-12 kDa, dialyze with deionized water for 3 days, and freeze-dry to obtain modified sodium hyaluronate;
[0041] S3: 80 g of raw silk was placed in 4 L of 0.0045 mol / L sodium carbonate aqueous solution and boiled for 3 times, each time for 30 min, rinsed with deionized water and dried at 55°C to obtain degummed fiber;
[0042] S4: 10 g of degummed fiber was dissolved in 100 mL of lithium bromide solution at 58°C and stirred for 60 min. After cooling, it was loaded into a dialysis bag with a molecular weight cutoff of 9-12 kDa, dialyzed with deionized water for 3-6 days, filtered with absorbent cotton, and then centrifuged at 10000 rpm for 5 min. After freeze-drying, an antidegradant was obtained.
[0043] The concentration of the lithium bromide solution is 9 mol / L;
[0044] S5: Dissolve 10g of sodium alginate in 500mL of deionized water, then add 50mL of 107g / L sodium periodate aqueous solution while stirring, add 3mL of ethylene glycol after 115min, continue to react for 55min, put into a dialysis bag with a molecular weight cutoff of 8-10kDa, dialyze with deionized water for 3d, and then freeze-dry to obtain a synergist;
[0045] S6: Add 12 g of modified sodium hyaluronate to 400 g of deionized water, adjust the pH to 7.3 with sodium hydroxide solution, then add 4.8 g of antidegradant and 7.2 g of synergist in sequence and mix well to obtain medical sodium hyaluronate gel;
[0046] Example 2: A method for preparing a medical sodium hyaluronate gel is as follows:
[0047] S1: 21 g of sodium hyaluronate powder with a molecular weight of 40-300 kDa was dissolved in 4300 g of deionized water, and then 12 g of N-hydroxysuccinimide and 29 g of carbodiimide were added in sequence, and the pH was adjusted to 4.7 with a hydrochloric acid solution, and activated for 1.8 hours to obtain a pre-modified sodium hyaluronate mixture;
[0048] S2: Add 18 g of cysteamine hydrochloride to 4362 g of the pre-modified sodium hyaluronate mixture, adjust the pH to 4.7 with sodium hydroxide solution, react for 24.3 h in a dark environment, put into a dialysis bag with a molecular weight cutoff of 8-12 kDa, dialyze with deionized water for 4 days, and freeze-dry to obtain modified sodium hyaluronate;
[0049] S3: 87 g of raw silk was placed in 4.3 L of 0.0047 mol / L sodium carbonate aqueous solution and boiled 4 times, each time for 32 min, rinsed with deionized water and dried at 57 °C to obtain degummed fiber;
[0050] S4: 12 g of degummed fiber was dissolved in 110 mL of lithium bromide solution at 59°C and stirred for 63 min. After cooling, it was loaded into a dialysis bag with a molecular weight cutoff of 9-12 kDa. After dialysis with deionized water for 3-6 days, it was filtered with absorbent cotton and then centrifuged at 10500 rpm for 6 min. After freeze-drying, the antidegradant was obtained.
[0051] The concentration of the lithium bromide solution is 9.1 mol / L;
[0052] S5: 12 g of sodium alginate was dissolved in 570 mL of deionized water, and then 60 mL of a 108 g / L sodium periodate aqueous solution was added while stirring. After 117 min, 3.5 mL of ethylene glycol was added, and the reaction was continued for 57 min. The mixture was placed in a dialysis bag with a molecular weight cutoff of 8-10 kDa, dialyzed with deionized water for 4 days, and then freeze-dried to obtain a synergist;
[0053] S6: Add 13 g of modified sodium hyaluronate to 430 g of deionized water, adjust the pH to 7.4 with a sodium hydroxide solution, then add 5.2 g of an antidegradant and 7.8 g of a synergist in sequence and mix well to obtain a medical sodium hyaluronate gel;
[0054] Example 3: A method for preparing a medical sodium hyaluronate gel is as follows:
[0055] S1: 24 g of sodium hyaluronate powder with a molecular weight of 40-300 kDa was dissolved in 4700 g of deionized water, and then 13 g of N-hydroxysuccinimide and 29.5 g of carbodiimide were added in sequence, and the pH was adjusted to 4.73 with hydrochloric acid solution, and activated for 1.9 hours to obtain a pre-modified sodium hyaluronate mixture;
[0056] S2: Add 19 g of cysteamine hydrochloride to 4766 g of the pre-modified sodium hyaluronate mixture, adjust the pH to 4.73 with sodium hydroxide solution, react for 2.7 h in a dark environment, put into a dialysis bag with a molecular weight cutoff of 8-12 kDa, dialyze with deionized water for 5 days, and freeze-dry to obtain modified sodium hyaluronate;
[0057] S3: 95 g of raw silk was placed in 4.7 L of 0.0048 mol / L sodium carbonate aqueous solution and boiled 4 times, each time for 34 min, rinsed with deionized water and dried at 57 °C to obtain degummed fiber;
[0058] S4: 14 g of degummed fiber was dissolved in 130 mL of lithium bromide solution at 61°C and stirred for 67 min. After cooling, it was loaded into a dialysis bag with a molecular weight cutoff of 9-12 kDa, dialyzed with deionized water for 5 days, filtered with absorbent cotton, and then centrifuged at 10700 rpm for 7 min. After freeze-drying, the antidegradant was obtained;
[0059] The concentration of the lithium bromide solution is 9.2 mol / L;
[0060] S5: 13 g of sodium alginate was dissolved in 700 mL of deionized water, and then 70 mL of 109 g / L sodium periodate aqueous solution was added while stirring. After 118 min, 4 mL of ethylene glycol was added. The reaction was continued for 57 min, and then the mixture was placed in a dialysis bag with a molecular weight cutoff of 8-10 kDa. The mixture was dialyzed with deionized water for 5 days and then freeze-dried to obtain a synergist.
[0061] S6: Add 14 g of modified sodium hyaluronate to 470 g of deionized water, adjust the pH to 7.4 with a sodium hydroxide solution, then add 5.6 g of an antidegradant and 8.4 g of a synergist in sequence and mix well to obtain a medical sodium hyaluronate gel;
[0062] Example 4: A method for preparing a medical sodium hyaluronate gel is as follows:
[0063] S1: 25 g of sodium hyaluronate powder with a molecular weight of 40-300 kDa was dissolved in 5000 g of deionized water, and then 14 g of N-hydroxysuccinimide and 30 g of carbodiimide were added in sequence, and then the pH was adjusted to 4.75 with hydrochloric acid solution, and activated for 2 hours to obtain a pre-modified sodium hyaluronate mixture;
[0064] S2: Add 20 g of cysteamine hydrochloride to 5069 g of the pre-modified sodium hyaluronate mixture, adjust the pH to 4.75 with sodium hydroxide solution, react for 25 h in a dark environment, put into a dialysis bag with a molecular weight cutoff of 8-12 kDa, dialyze with deionized water for 6 days, and freeze-dry to obtain modified sodium hyaluronate;
[0065] S3: 100 g of raw silk was placed in 5 L of 0.005 mol / L sodium carbonate aqueous solution and boiled for 5 times, each time for 35 min, rinsed with deionized water and dried at 60° C. to obtain degummed fiber;
[0066] S4: 15 g of degummed fiber was dissolved in 140 mL of lithium bromide solution at 62° C. and stirred for 70 min. After cooling, it was loaded into a dialysis bag with a molecular weight cutoff of 9-12 kDa, dialyzed with deionized water for 3-6 days, filtered with absorbent cotton, and then centrifuged at 11000 rpm for 8 min. After freeze-drying, the antidegradant was obtained;
[0067] The concentration of the lithium bromide solution is 9.3 mol / L;
[0068] S5: 15 g of sodium alginate was dissolved in 750 mL of deionized water, and then 75 mL of 110 g / L sodium periodate aqueous solution was added while stirring. After 120 min, 4.5 mL of ethylene glycol was added. After the reaction was continued for 60 min, the mixture was placed in a dialysis bag with a molecular weight cutoff of 8-10 kDa, dialyzed with deionized water for 6 days, and then freeze-dried to obtain a synergist;
[0069] S6: Add 15 g of modified sodium hyaluronate to 500 g of deionized water, adjust the pH to 7.5 with sodium hydroxide solution, then add 6 g of antidegradant and 9 g of synergist in sequence and mix well to obtain medical sodium hyaluronate gel;
[0070] Comparative Example 1:
[0071] Compared with Example 1, this comparative example only replaces "modified sodium hyaluronate" with "sodium hyaluronate powder with a molecular weight of 40-300 kDa", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a sodium hyaluronate gel is obtained;
[0072] Comparative Example 2:
[0073] Compared with Example 1, this comparative example only replaces the "dialysis bag with a molecular weight cutoff of 9-12 kDa" used in the preparation process of the antidegradant with a "dialysis bag with a molecular weight cutoff of 8-10 kDa", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally obtains sodium hyaluronate gel;
[0074] Comparative Example 3:
[0075] Compared with Example 1, this comparative example only replaces the "dialysis bag with a molecular weight cutoff of 8-10 kDa" used in the preparation process of the synergist with a "dialysis bag with a molecular weight cutoff of 9-12 kDa", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally obtains sodium hyaluronate gel;
[0076] Comparative Example 4:
[0077] Compared with Example 1, this comparative example only replaces the "anti-degradation agent" added in the preparation process of sodium hyaluronate gel with a "synergist", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally obtains sodium hyaluronate gel;
[0078] Comparative Example 5:
[0079] Compared with Example 1, this comparative example only replaces the "enhancer" added in the preparation process of sodium hyaluronate gel with an "anti-degradant", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally sodium hyaluronate gel is obtained.
[0080] Performance Test:
[0081] Determination of anti-degradation ability:
[0082] Dissolve 0.2g potassium chloride, 0.2g potassium dihydrogen phosphate, 8.0g sodium chloride, and 2.88g sodium hydrogen phosphate dodecahydrate in deionized water and adjust the volume to 100mL to obtain a PBS solution; place the hydrogel in an empty centrifuge tube, and record the weights W and W1 of the centrifuge tube before and after placement. The weight change is the initial mass of the hydrogel Wa=W1-W, and then inject 30ml of PBS solution into the centrifuge tube as a degradation solution, and place it in a 37°C incubator for constant incubation. After 24 hours, pour out the degradation solution, lightly wipe the surface of the hydrogel and the inside of the centrifuge tube with absorbent paper, and re-weigh to obtain W2, then the remaining hydrogel mass is Wc=Wa-W2. According to this method, the anti-degradation ability (%) of the sodium hyaluronate gel prepared in Example 1-Example 4 and Comparative Example 1-Comparative Example 5 is calculated, and the anti-degradation ability calculation formula is as follows;
[0083] The calculation formula of anti-degradation ability is:
[0084] Cytotoxicity assay:
[0085] Referring to the test standard GB / T16886.5-2017 "Biological Evaluation of Medical Devices Part 5: In Vitro Cytotoxicity", the cytotoxicity was tested by extraction method, the immersion time was 24h, and the test cells were HFF-1 cells. Positive control group: 5% by mass of dimethyl sulfoxide; experimental group: sodium hyaluronate gel prepared by Examples 1-4 and Comparative Examples 1-5; the cytotoxicity reaction level is divided into the following 5 levels: Level 0: relative growth rate ≥ 100%; Level 1: relative growth rate of 80%-99%; Level 2: relative growth rate of 50%-79%; Level 3: relative growth rate of 30%-49%; Level 4: relative growth rate of ≤29%;
[0086] Determination of antibacterial ability:
[0087] Six circular filter papers with a diameter of 6 mm were placed in the sodium hyaluronate gels prepared in Examples 1 to 4 and Comparative Examples 1 to 5, respectively, and sterilized under the same high-pressure steam (120° C., 0.12 MPa) for 10 min. 100 uL of the bacterial suspension was evenly applied on the surface of the culture medium plate, and each filter paper was attached to the bacterial plate with sterile tweezers. The plates were cultured at 37° C. for 24 h, and the antibacterial zone diameters of the six circular filter papers were measured and the average value was calculated as the antibacterial ability of the corresponding sodium hyaluronate gel. The antibacterial zone diameter greater than 10 mm was qualified.
[0088] Determination of water replenishment capacity:
[0089] 450 volunteers were randomly divided into 9 groups, each with 50 people. The first group used and evaluated the sodium hyaluronate gel prepared in Example 1, the second group used and evaluated the sodium hyaluronate gel prepared in Example 2, the third group used and evaluated the sodium hyaluronate gel prepared in Example 3, the fourth group used and evaluated the sodium hyaluronate gel prepared in Example 4, the fifth group used and evaluated the sodium hyaluronate gel prepared in Comparative Example 1, the sixth group used and evaluated the sodium hyaluronate gel prepared in Comparative Example 2, the seventh group used and evaluated the sodium hyaluronate gel prepared in Comparative Example 3, the eighth group used and evaluated the sodium hyaluronate gel prepared in Comparative Example 4, and the ninth group used and evaluated the sodium hyaluronate gel prepared in Comparative Example 5. The evaluation criteria were "satisfactory" (good skin moisturizing) and "general" (dry skin). The measurement results are shown in Table 1.
[0090] Table 1
[0091]
[0092] Data Analysis:
[0093] As can be seen from Table 1, the sodium hyaluronate gel prepared by the present invention has stronger anti-degradation ability, antibacterial ability, water replenishment ability, and extremely low cytotoxicity;
[0094] This may be because the cross-linking agent used in the modification of sodium hyaluronate in the present invention has lower toxicity, and the present invention also performs dialysis treatment on it during the modification process, that is, modified sodium hyaluronate with a specific molecular weight is obtained, and its toxicity is further reduced. At the same time, the added antidegradation agent and synergist are also non-toxic substances. Therefore, the sodium hyaluronate gel prepared by the present invention has extremely low toxicity; and the present invention performs dialysis treatment during the preparation process of the antidegradation agent, synergist, and modified sodium hyaluronate. By using a dialysis bag with a specific molecular weight cutoff, antidegradation agents, synergists, and modified sodium hyaluronate that can be cross-linked with each other are obtained, so that the antidegradation ability of the sodium hyaluronate gel is further improved; and the active ingredients rich in the antidegradation agent obtained by degumming raw silk and heat-treating it with a lithium bromide solution improve the antibacterial ability and moisturizing ability of the sodium hyaluronate gel of the present invention.
[0095] As for Comparative Example 1, since "modified sodium hyaluronate" is replaced with "sodium hyaluronate powder with a molecular weight of 40-300 kDa", it can be seen from Table 1 that compared with Example 1, its anti-degradation ability, antibacterial ability and water replenishment ability are all reduced. This may be because after the modification, thiol groups are generated on the side chains of sodium hyaluronate, and the thiol groups can react with the phenolic hydroxyl groups in the antidegradation agent and the synergist, thereby increasing the crosslinking degree between sodium hyaluronate and the antidegradation agent and the synergist, so that the sodium hyaluronate gel of the present invention has higher anti-degradation ability, antibacterial ability and water replenishment ability;
[0096] In Comparative Example 2, the "dialysis bag with a molecular weight cutoff of 9-12 kDa" used in the preparation of the antidegradant is replaced by a "dialysis bag with a molecular weight cutoff of 8-10 kDa"; in Comparative Example 3, the "dialysis bag with a molecular weight cutoff of 8-10 kDa" used in the preparation of the synergist is replaced by a "dialysis bag with a molecular weight cutoff of 9-12 kDa"; as can be seen from Table 1, compared with Example 1, their antidegradation abilities are all reduced, which may be due to the fact that the antidegradant with a molecular weight of 9-12 kDa, the synergist with a molecular weight of 8-10 kDa, and the modified sodium hyaluronate with a molecular weight of 8-12 kDa are relatively better cross-linked with each other, and the cross-linked hydrogel network is more stable and has a stronger anti-degradation ability;
[0097] In Comparative Example 4, the "antidegradation agent" added in the preparation process of sodium hyaluronate gel is replaced by a "synergist"; in Comparative Example 5, the "synergist" added in the preparation process of sodium hyaluronate gel is replaced by an "antidegradation agent"; as can be seen from Table 1, compared with Example 1, their antidegradation ability, antibacterial ability, and moisturizing ability are all reduced, among which the moisturizing ability of Comparative Example 4 is more seriously reduced. This may be because the synergist can improve the stability of the hydrogel cross-linked network, and the antidegradation agent and the active ingredients contained therein are the key to the formation of the hydrogel cross-linked network, the improvement of the water-retaining and moisturizing ability of the hydrogel, and the antibacterial and antibacterial ability.
[0098] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0099] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing medical sodium hyaluronate gel, characterized in that: The following steps are involved: Add modified sodium hyaluronate to deionized water, adjust the pH to 7.3-7.5 with sodium hydroxide solution, then add antidegradant and synergist in sequence and mix well to obtain medical sodium hyaluronate gel; The mass ratio of the deionized water, modified sodium hyaluronate, antidegradant and synergist is 400-500:12-15:4.8-6:7.2-9; The modified sodium hyaluronate is prepared from sodium hyaluronate powder, N-hydroxysuccinimide, carbodiimide, and cysteamine hydrochloride; The antidegradation agent is prepared by heat-treating raw silk with lithium bromide solution after degumming; The synergist is prepared from sodium alginate, sodium periodate and ethylene glycol.
2. The method for preparing medical sodium hyaluronate gel according to claim 1, characterized in that: The preparation method of the modified sodium hyaluronate is as follows: Step A1: dissolving sodium hyaluronate powder in deionized water, then sequentially adding N-hydroxysuccinimide and carbodiimide, and then adjusting the pH to 4.7-4.75 with hydrochloric acid solution, and activating for 1.7-2 hours to obtain a pre-modified sodium hyaluronate mixture; Step A2: Add cysteamine hydrochloride to the pre-modified sodium hyaluronate mixture, adjust the pH to 4.7-4.75 with sodium hydroxide solution, react for 24-25 hours under light-proof conditions, put into a dialysis bag, dialyze with deionized water for 3-6 days, and obtain modified sodium hyaluronate after freeze-drying.
3. The method for preparing the medical sodium hyaluronate gel according to claim 2, characterized in that: The molecular weight of the sodium hyaluronate powder in step A1 is 40-300 kDa; The mass ratio of the sodium hyaluronate powder, deionized water, N-hydroxysuccinimide and carbodiimide in step A1 is 20-25:4000-5000:11.5-14:28.7-30.
4. The method for preparing the medical sodium hyaluronate gel according to claim 2, characterized in that: The mass ratio of the pre-modified sodium hyaluronate mixture and cysteamine hydrochloride in step A2 is 4060-5069:17-20; The molecular weight cut-off of the dialysis bag in step A2 is 8-12 kDa.
5. The method for preparing the medical sodium hyaluronate gel according to claim 1, characterized in that: The preparation method of the antidegradant is as follows: Step B1: boiling raw silk in a sodium carbonate aqueous solution for 3-5 times, each time for 30-35 minutes, rinsing with deionized water and drying at 55-60° C. to obtain degummed fibers; Step B2: dissolving the degummed fiber in a lithium bromide solution at 58-62° C. and stirring for 60-70 minutes, putting the fiber into a dialysis bag after cooling, dialyzing it with deionized water for 3-6 days, filtering it with absorbent cotton, centrifuging it at 10000-11000 rpm for 5-8 minutes, and freeze-drying it to obtain an antidegradant.
6. The method for preparing medical sodium hyaluronate gel according to claim 5, characterized in that: In step B1, the ratio of raw silk to sodium carbonate aqueous solution is 80-100 g: 4-5 L; The concentration of the sodium carbonate aqueous solution in step B1 is 0.0045-0.005 mol / L.
7. The method for preparing medical sodium hyaluronate gel according to claim 5, characterized in that: The degummed fiber and lithium bromide solution in step B2 are used in a ratio of 10-15 g: 100-140 mL; The concentration of the lithium bromide solution in step B2 is 9-9.3 mol / L; The molecular weight cut-off of the dialysis bag in step B2 is 9-12 kDa.
8. The method for preparing medical sodium hyaluronate gel according to claim 1, characterized in that: The preparation method of the synergist is as follows: Sodium alginate was dissolved in deionized water, and then sodium periodate aqueous solution was added while stirring. Ethylene glycol was added after 115-120 minutes, and the reaction was continued for 55-60 minutes. The mixture was put into a dialysis bag, dialyzed with deionized water for 3-6 days, and then freeze-dried to obtain a synergist.
9. The method for preparing medical sodium hyaluronate gel according to claim 8, characterized in that: The concentration of the sodium periodate aqueous solution is 107-110 g / L.
10. The method for preparing medical sodium hyaluronate gel according to claim 8, characterized in that: The dosage ratio of the sodium alginate, deionized water, sodium periodate aqueous solution, and ethylene glycol is 10-15 g: 500-750 mL: 50-75 mL: 3-4.5 mL; The molecular weight cut-off of the dialysis bag is 8-10 kDa.